Financial Literacy of Students: University Case Studies in Indonesia - Arinal Muna; Andi Sri Wahyuni; Ayatulloh Michael Musyaffi (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2022)
The purpose of this research is to examine student financial literacy in Indonesia. A case study is used as a design method to analyze and explore the financial lives of students at Swadaya Gunung Jati University. By using descriptive statistics, this paper has demonstrated that more than half of students who participate in financial literacy can manage their finances wisely. The present findings have important implications for developing the curriculum in financial management subject in Indonesia, precisely in managing finances for students’ daily life, which ignoring by the majority of financial management courses in Indonesian universities.